Saudi EFL Learners’ Response to Different Grammar Tasks - Alanazi, Sami (JOURNAL OF ADVANCES IN LINGUISTICS, 2018)
This study examines intermediate level adult EFL students in Saudi Arabia, and the effectiveness of task-based learning in relation to their understanding of English grammar. The students were given three different tasks related to negative adverbs, designed to help them learn past-tense verb forms in English. There were three groups of 20 students, all of whom were learning at the same level. The groups were: Selected response group (SRG, n=20) Constrained constructed response group (CCR, n=20) Storytelling group (FRG, n=20) Each group was given a pre-test to determine their level before the tasks, a test immediately after, and a delayed test. The selected response group (SRG) performed best on the tests, demonstrating the effectiveness of taskbased teaching in grammar acquisition. Students were chosen at random for an interview, in which their grammar knowledge was assessed. This produced results that mirrored those of the tests. It was also clear that the kinds of tasks chosen by teachers had an impact on the effectiveness of their lessons. This study provides EFL teachers with vital information they can use in learning design and lesson planning and gives EFL students information they can use to support their own learning.